A systems model for the design of occupational health and safety management systems inclusive of work-from-home arrangements. (May 2023) - Bentley, Tim A.; Caponecchia, Carlo; Onnis, Leigh-ann; Brunetto, Yvonne; Farr-Wharton, Ben; Cattani, Marcus; Neto, Abilio; Vassiley, Alexis
Abstract: The study addressed an important knowledge gap in the literature by co-designing a model for OHS management systems inclusive of workers who work-from-home, with a focus on psychosocial risks. This qualitative research study utilised a series of co-design focus groups involving Australian regulators, health and safety managers and practitioners, senior managers, middle managers and workers who work-from-home, to better understand the types of measures that organisations can apply to improve their health and safety management systems. Using a systems approach, consideration was given to the organisation of the remote working system, the home-work interface for remote workers, the competencies of managers and employees in regard to their occupation health and safety (OHS) responsibilities, and the complexity of identifying, reporting and monitoring psychosocial hazards for employees working from home. The study identified a need for tools designed to support both managers and workers in promoting psychologically safe working from home. Highlights: OHS systems developed for traditional workplaces do not support working from home. Systems are needed to support psychological safety for working from home. Working from home challenged perceptions of OHS obligations such as rights of entry. Barriers to hazard management include poor understanding of psychosocial risks. There is a need for measures to increase the participation of remote workers in OHS.